Return to sender: a behavioural approach to reducing food waste in schools. Issue 4 (2nd October 2019) - Boulet, M.; Wright, B.; Williams, C.; Rickinson, M.
ABSTRACT: Waste is an inherent part of the global food system, with significant environmental, social and economic impacts. Rather than simply managing its disposal, addressing the food waste challenge in Australia requires engagement with consumers to encourage behaviours that reduce wastage. This exploratory case study utilised a behavioural approach to identify and prioritise food waste reduction behaviours in Western Australian schools and then analysed these behaviours from the perspective of key target audiences. This enabled appropriate interventions to be proposed for testing. It offers a targeted approach to tackle food waste in schools and the wider community.